Analisis Efektivitas Penerimaan Pajak Bumi Dan Bangunan (PBB) di Kecamatan Tolangohula Kabupaten Gorontalo - Barmin Yusuf (Gorontalo Development Review, 2018)
Land and Building Tax is a potential source of revenue for the region as one of the direct taxes. Land and Building Tax is a central tax because the object is in the area, then the region gets a bigger share. In Gorontalo Regency, mainly Tolagohula Sub-district, as in other parts of Indonesia, the land and property tax (PBB) is one source of local revenue. The management of the land and building tax (PBB) in Tolangohula sub-district is expected to lead to the welfare of the people in Gorontalo Regency.The purpose of this study is to determine how the effectiveness of tax revenue Earth and Building (PBB) in District Tolangohula Gorontalo District. Using the Ratio of the effectiveness of Land and Building Tax revenues (PBB) shows the ability of local governments in mobilizing Land and Building Tax (PBB) in accordance with the targeted. The ability to obtain Land and Building Tax (PBB) is categorized effective if this ratio reaches at least 1 or 100%. Overall, the acceptance effectiveness of Land and Building Tax (PBB) in District Tolangohula Regency Gorontalo during the period of 2012 to 2014 is in the effectiveness category.